An FSO-Based Drone Assisted Mobile Access Network for Emergency Communications - Wu, Di; Sun, Xiang; Ansari, Nirwan (IEEE transactions on network science and engineering, 2020)
Deploying drone mounted base stations (DBSs) can quickly recover communications of mobile users (MUs) in a disaster struck area. That is, DBSs can act as relay nodes to transmit data from remote working base stations (which are located out of the disaster struck area) to MUs. Since DBSs could be deployed very close to MUs, the access link data rates between DBSs and MUs are well provisioned. However, DBSs may be far away from the remote working base stations, and thus the backhaul link data rate between a DBS and the remote working base station could be throttled. Free Space Optics (FSO), which has been demonstrated to provision high speed point-to-point wireless communications, can be leveraged to improve the capacity of the backhaul link. Since FSO requires line-of-sight between a DBS and a remote working macro base station, DBSs have to be carefully deployed. In this paper, we design a QoS awaRe dronE base Station plaCement and mobile User association stratEgy (RESCUE) in the context of FSO based drone assisted mobile access networks to jointly optimize the DBS deployment, MU association, and bandwidth allocation such that the number of served MUs in the disaster struck area is maximized. The performance of RESCUE is validated via extensive simulations.